Mixed Connective Tissue Disease Highlighting Diagnostic Exigency and Treatment Woes - Nagma, Sabahat Zamani; Afsar, Nabila; Afroze, Idrees Akhtar; Begum, Atiya (Annals of Pathology and Laboratory Medicine, 2019)
Mixed connective tissue disease (MCTD) is a rare connective tissue disease characterized by manifestations that overlap symptoms typical of several other inflammatory diseases of connective tissue. A presence of anti-ribonucleoprotein antibodies (antiU1RNP) in high titer is a typical immunological finding. A 20 year old female complained of chilling and cyanosis of fingers on cold exposure since 5 years, with pain and numbness, hardening of skin of both hands, episodes of Raynaud’s phenomenon,gangrenous changes, self amputation of distal digit of middle finger. Systemic manifestations were also associated. A 15 year old female complained of thickening and tightening of skin of face and hands since 5 months, associated with joint pains, shortness of breath, dysphagia and photosensitivity of skin. Both cases were positive for Anti U1-RNP and Anti-SSA/Ro52 antibodies. Serology, radiology and histopathology were performed.. MCTD may be difficult to define as definite classification criteria are not fulfilled. Young and pediatric patients with skin manifestations must be investigated to initiate early treatment and monitor renal parameters. Patient compliance and trust in treating physician is a key to early diagnosis and treatment. Treating physician must recognize symptoms and refer patients to higher centres.